Validity of dynamic capabilities in the operation based on new sustainability narratives on nature tourism SMEs and clusters (2020)
This study aims to validate the relationships between the dynamic capabilities in the operation of small and medium enterprises (SMEs) that constitute the Nature Tourism Cluster (also known as 'ecotourism') in Colombia, through the application of surveys to managers and owners of hotels and lodgings of rural tourism, travel agencies, tour guides and operators, bars, restaurants and tourist transport centers, whose data obtained, support our hypothesis that the dynamic capacities of absorption, adaptation and innovation influence the functioning of SMEs, while at the cluster level, there is an positive relationship in the interaction of absorption and innovation capabilities. The greatest contribution of our research consists in the development of an empirical study that is based on the main contributions of the dynamic capabilities promoted by Teece (absorption, adaptation and innovation), and that allowed to determine the degree of influence that managers have to take decisions and undertake sustainable ecotourism actions, both at the SME level and at the cluster level. For this reason, our research provides a better understanding of how dynamic capabilities operate at the individual commercial level, as well as at the cluster level, in the combination of absorption, adaptation and innovation capabilities to foster new sustainability narratives and maintain sustainable ecotourism. Our results also point out the limitations and challenges for the sustainable tourism sector in Colombia. © 2020 by the authors.